2008
DOI: 10.1017/s0021932007002672
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Use of Modern Contraceptives and Implications for Woman-Controlled Prevention of Sexually Transmitted Infections in Madagascar

Abstract: SUMMARYGlobally, unplanned pregnancies and sexually transmitted infections (STIs) persist as significant threats to women's reproductive health. Barriers to the use of modern contraceptives by women might inhibit uptake of novel woman-controlled methods for preventing STIs/HIV. Use of modern contraceptives and perceptions and attitudes towards contraceptive use were investigated among women in Antananarivo, Madagascar using qualitative research. The hypothetical acceptability of the diaphragm, a woman-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Ignorance and misinformation were leading barriers to contraceptive use. This corroborates several other studies 21,22. Higher awareness would stimulate community members to look for more accurate information on desired methods from health care providers and consequently, promote correct and consistent use of the method.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ignorance and misinformation were leading barriers to contraceptive use. This corroborates several other studies 21,22. Higher awareness would stimulate community members to look for more accurate information on desired methods from health care providers and consequently, promote correct and consistent use of the method.…”
Section: Discussionsupporting
confidence: 89%
“…Globally, unplanned pregnancies and sexually transmitted infections (STIs) persist as significant threats to women’s reproductive health 2. Barriers to the use of modern contraceptives by women might inhibit uptake of novel woman-controlled methods for preventing unwanted pregnancies and STIs/human immunodeficiency virus (HIV).…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study conducted by others in our group indicated that, among women seeking care at public health clinics in Antananarivo, negative perceptions of hormonal contraception’s side effects, namely, weight gain, prevented hormonal contraceptive use [21]. Concerns about side effects and inconvenience of contraception have become the most important factors driving unmet need in the developing world [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that perceptions of whether male partners are supportive of contraceptive use can influence whether women use contraception [ 16 22 ]. For example, concern about opposition to contraceptive use, mainly from male partners, was identified as a barrier to contraceptive use among women in Madagascar [ 23 ]. Additional research has found that involving men in contraceptive counseling was associated with increased contraceptive use [ 24 – 27 ], though other studies have found negative or no effects [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%